Essential APSES Transcription Factors for Mycotoxin Synthesis, Fungal Development, and Pathogenicity in Aspergillus flavus - Yao, Guangshan; Zhang, Feng; Nie, Xinyi; Wang, Xiuna; Yuan, Jun; Zhuang, Zhenhong; Wang, Shihua (Frontiers in Microbiology, 2017)
Aflatoxins are a potent carcinogenic mycotoxin and has become a research model of fungal secondary metabolism (SM). Via systematically investigating the APSES transcription factors (TFs), two APSES proteins were identified: AfRafA and AfStuA. These play central roles in the synthesis of mycotoxins including aflatoxin and cyclopiazonic acid, and fungal development and are consequently central to the pathogenicity of the aflatoxigenic A. flavus. Loss of AfRafA not only dramatically suppressed aflatoxin cluster expression, subsequently reducing toxin synthesis both in vitro and in vivo, but also impaired conidia and sclerotia development. More importantly, aflatoxin biosynthesis as well as conidia and sclerotia development were fully blocked in ΔAfStuA. In addition, our results supported that AfStuA regulated the aflatoxin synthesis in an AflR-dependent manner. Intriguingly, it was revealed that AfRafA and AfStuA exert an antagonistic role in the regulation of biosynthesis of cyclopiazonic acid. In summary, two global transcriptional regulators for fungal development, mycotoxin production, and seed pathogenicity of the A. flavus system have been established. The two novel regulators of mycotoxins are promising targets for future plant breeding and for the development of fungicides.